Recombinant protein production from transgenic animals: Systems and applications - Alvarado-Madrigal, María Fernanda (2019)
The use of transgenic animals for the production of recombinant proteins for therapeutic purposes has been an alternative used for the production of drugs. The ability to make complex post-translational modifications in an efficient manner is an advantage that this type of technology has over the use of other transgenic organisms. For this reason, different transgenic animals (ruminants, rabbits, pigs, birds and insects) have been developed over the years and different systems (milk, egg, blood, urine and seminal fluid) have been studied to obtain recombinant proteins. Each animal and each system has advantages and disadvantages, which should be considered before starting the productive process of the protein of interest. Drugs such as ATryn®, Ruconest® and Kanuma® have already been approved by the FDA for human administration. The future of this type of preparations must be considered, given that there are several therapeutic proteins that are in the research phase or waiting to be approved and commercialized.